2021
DOI: 10.1021/acs.cgd.1c00299
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ and Real-Time Plasmonic Approach of Seed/Adhesion Layers: Chromium Buffer Effect at the Zinc/Alumina Interface

Abstract: The eect of additives on metal/oxide interfaces is explored in situ and in real time on evaporated lms by a combination of surface science techniques, among which a very exible optical method shows a unique ability to scrutinize the growth and wetting properties of supported clusters that involve several elements. The study focuses on Cr at the Zn/α-Al 2 O 3 (0001) interface at 300 K. A particular interest of the present interface is that Zn does not stick at all on bare alumina. The sticking and morphology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 101 publications
(269 reference statements)
1
9
0
Order By: Relevance
“…The standard MTJ structure for STT-MRAM and VC-MRAM is CoFeB/MgO/CoFeB with bottom-pinned and top-free CoFeB layers because this trilayer structure can be fabricated on (111)-textured Co/Pt multilayers with a very high PMA, which gives rise to the pinning force of the bottom-pinned CoFeB layer. , However, the top CoFeB layer of this standard structure tends to have low quality because island-like initial growth of CoFeB occurs on the MgO(001) surface, reflecting the poor wettability of CoFeB on MgO(001) caused by the low surface energy of MgO(001). The island-like initial growth results in a rougher CoFeB layer, which degrades magnetic properties such as the TMR ratio and PMA, particularly when the CoFeB layer is ultrathin. ,, Therefore, developing deposition processes to achieve a high-quality ultrathin CoFeB layer on MgO is of considerable importance for next-generation STT-MRAM and VC-MRAM. The quality of the CoFeB/MgO interface is also very important because PMA, TMR, and VCMA effects are interface-sensitive phenomena. …”
Section: Introductionmentioning
confidence: 99%
“…The standard MTJ structure for STT-MRAM and VC-MRAM is CoFeB/MgO/CoFeB with bottom-pinned and top-free CoFeB layers because this trilayer structure can be fabricated on (111)-textured Co/Pt multilayers with a very high PMA, which gives rise to the pinning force of the bottom-pinned CoFeB layer. , However, the top CoFeB layer of this standard structure tends to have low quality because island-like initial growth of CoFeB occurs on the MgO(001) surface, reflecting the poor wettability of CoFeB on MgO(001) caused by the low surface energy of MgO(001). The island-like initial growth results in a rougher CoFeB layer, which degrades magnetic properties such as the TMR ratio and PMA, particularly when the CoFeB layer is ultrathin. ,, Therefore, developing deposition processes to achieve a high-quality ultrathin CoFeB layer on MgO is of considerable importance for next-generation STT-MRAM and VC-MRAM. The quality of the CoFeB/MgO interface is also very important because PMA, TMR, and VCMA effects are interface-sensitive phenomena. …”
Section: Introductionmentioning
confidence: 99%
“…However, this strategy faces intrinsic limits, in terms of technical feasibility and final grain boundary density which drives the film resistivity and its stress state to a large extent. Engineering solutions based on the use of so-called buffer layers (see ref and all references therein) or “surfactants” have been devised to obtain thinner but continuous films. These buffer layers, most of the time made of transition metals or the corresponding metal parent oxides, improve the metal island wettability on the substrate by replacing relatively weak substrate/noble metal bonds with stronger metal/metal and metal/substrate bonds, increasing the sticking coefficient and changing the growth dynamics .…”
Section: Introductionmentioning
confidence: 99%
“…Engineering solutions based on the use of so-called buffer layers (see ref and all references therein) or “surfactants” have been devised to obtain thinner but continuous films. These buffer layers, most of the time made of transition metals or the corresponding metal parent oxides, improve the metal island wettability on the substrate by replacing relatively weak substrate/noble metal bonds with stronger metal/metal and metal/substrate bonds, increasing the sticking coefficient and changing the growth dynamics . A limitation in buffer thickness is nonetheless often encountered for the final properties, in particular optical transmittance.…”
Section: Introductionmentioning
confidence: 99%
“…14 Hence, state-ofthe-art surfactant-based strategies are not unconditionally relevant for manipulating film growth on weakly-interacting substrates. Despite the latter, empirical studies have shown that the use transition-metal and semiconducting alloying agents and seed layers, [23][24][25][26][27][28][29] as well deployment of gaseous species 9,[30][31][32][33][34][35] can effectively reverse the tendency toward 3D morphology in Ag and Cu layers on oxide substrates. Concurrently, potential incorporation of alloying species in the film, as well as modification of the film/substrate 4 interface due to the presence of seed layers may affect other physical (e.g., optoelectronic) properties of the noble-metal layer and the overall performance of the corresponding heterostructure device.…”
Section: Introductionmentioning
confidence: 99%